Joseph Beuys : Early drawings - Schade, Werner (New York : W.W. Norton & Company, 1992)
This extensive collection of drawings is a groping attempt to address the anthropos, the human race in its spiritual manifestations in various cultures. Perhaps I'm a reborn cave artist transposed into a culture that bombards me with such elemental questions, placing human diginity and the dignity of nature and animals into the center of immediate personal experience. This first awareness of what is being exterminated and destroyed in our world is the beginning of a theory of sculpture... is a logical beginning, and this brings forth an abundant world of images from which concepts gradually emerge. (Joseph Beuys)
geselect. bibliog. p. 103
korte biog. p. 100-102
Engels
boek
Keywords: Beuys, Joseph